Public Participation in the Revitalization of Kütahya's CBD in Turkey - Berk Minez; Nevnihal Erdogan (European Regional Science Association (ERSA), 2006)
Abstract Kütahya has been the crade of many cultures throughout the history. Especially, its population grew after Turkish occupation and the city expanded beyond the walls of the city. Traditional life characteristics and tradational production stiles survived till how such as ceramics, textile, leather, carpets and handcrafts. Thus, Centre Business District (CBD) continue to preservative the business vitality together with religious, social and civil architecture examples and its conservative people. So, if the preservation aims the participation of public (owners/users), the social pattern of the area becomes so important in the process. With determining the relation between the social and physical attitudes towards the preservation of the area, suitable solution can be formed which fits with the situation. A social survey was conducted to the offices. The results of the survey related with ownership patterns, the functions, the employee and customers of the shop, the consciousness and tendencies to repair activities. Thus, the results of the study can be useful for policy makers, urban planners and inverts.
Keywords: 330